Metabolomics: a brief introduction 1 - Salek, Reza (Henry Stewart Talks, 2018)
Early metabolomics, Biomarker diagnosis & monitoring, Metabolomics on a chip, Omics by numbers, Cell size vs. metabolite, Dynamic range of metabolome, Snapshot metabolomics